Higher rates of mental health screening of adolescents recorded after provider training using simulated patients in a Kenyan HIV clinic: results of a pilot study - Concepcion, Tessa; Mogere, Peter; Ngure, Kenneth; Mwathi, Njoroge; Njiru, Roy; Kipkorir, Boaz; Kiptinness, Catherine; Maina, Gakuo; Owidi, Emmah; Owens, Tamara; Kohler, Pamela; Wagenaar, Bradley H.; et al. (Frontiers in Public Health, 2023)
Background: Kenyan adolescent girls and young women (AGYW) experience a dual burden of HIV and common mental disorders (CMD). HIV clinics are a key entry point for AGYW in need of integrated CMD and HIV care; however, rates of screening and referral for CMDs are low. Our objective was to test an evidence-based provider training strategy, simulated patient encounters (SPEs), on CMD service delivery for AGYW in a Kenyan HIV clinic.Methods: This pilot study was conducted in a public HIV clinic in Thika, Kenya from January to November 2021. The simulated patient encounter (SPE) implementation strategy included case script development from prior qualitative work, patient actor training, and a three-day SPE training including four standardized mock clinical encounters followed by quantitative surveys assessing provider competencies for each encounter. We abstracted medical record data related to HIV and CMDs such as HIV status, reason for visit, CMD screening test performed, and counselling or referral information. We conducted an interrupted time series analysis using abstracted HIV and CMD screening rates from AGYW ages 16-25 years visiting the clinic 7-months before and 3months after SPE training. We used generalized linear models to assess changes in CMD screening rates after training.Results: A total of 10 providers participated in the training. Competency ratings improved across four mock encounters (mean score from 8.1 to 13.7) between first and fourth encounters. We abstracted all medical records (n=1154) including from 888 (76%) AGYW seeking HIV treatment, 243 (21%) seeking prevention services, and 34 (3%) seeking other services. CMD screening rates increased immediately following training from 8% to 21% (relative risk [RR]=2.57, 95% confidence interval [CI]=1.34-4.90, p<0.01). The three months following the SPE training resulted in an 11% relative increase in CMD screening proportion compared to the seven months pre-SPE (RR: 1.11, 95% CI: 1.04 -1.17, p<0.01). Finally, 1% of all pre-SPE screens resulted in referral versus 5% of post-SPE screens (p=0.07).The SPE model is a promising implementation strategy for improving HIV provider competencies and CMD service delivery for adolescents in HIV clinics. Future research is needed to explore effects on adolescent clinical outcomes in larger trials.